Has the Standard Cognitive Reflection Test Become a Victim of Its Own Success? - Haigh, Matthew (Adv Cogn Psychol, 2016)
The Cognitive Reflection Test (CRT) is a hugely influential problem solving task that measures individual differences in the propensity to reflect on and override intuitive (but incorrect) solutions. The validity of this three-item measure depends on participants being naïve to its materials and objectives. Evidence from 142 volunteers recruited online suggests this is often not the case. Over half of the sample had previously seen at least one of the problems, predominantly through research participation or the media. These participants produced substantially higher CRT scores than those without prior exposure (2.36 vs. 1.48), with the majority scoring at ceiling level. Participants that had previously seen a specific problem (e.g., the bat and ball problem) nearly always solved that problem correctly. These data suggest the CRT may have been widely invalidated. As a minimum, researchers must control for prior exposure to the three problems and begin to consider alternative, extended measures of cognitive reflection.